1958
DOI: 10.1103/physrev.109.1916
|View full text |Cite
|
Sign up to set email alerts
|

Semiconducting Properties ofMg2Ge Single Crystals

Abstract: Single crystals of Mg&Ge have been obtained from melts of the constituents, and Hall effect and electrical resistivity measurements have been made from 77'K to 1000'K. Undoped crystals were n-type and had saturated impurity carrier concentration as low as 3X10" cm; silver-doped crystals were P-type and had saturated impurity carrier concentrations roughly proportional to the amount of added silver. The room-temperature Hall rnobilities were observed to be 280 cm'/volt-sec for electrons and 110 cm'/volt-sec for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

1967
1967
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(30 citation statements)
references
References 3 publications
4
26
0
Order By: Relevance
“…The temperature dependence of the undoped and lightly doped crystals A and B agrees closely with data from earlier investigations on pure Mg 2 Sn single crystals, 8 the data from the heavily doped crystals are in broad agreement with data for Mg 2 Si and Mg 2 Ge crystals. [17][18][19] It is noted that the decrease in resistivity is consistent with the increase in carrier concentration, and any significant variations in the absolute resistivity values are likely due to uneven dopant distribution and the likely presence of microcracks. Samples with a small amount of free Sn show a transition to a lower residual resistivity at about 3.5 K (not shown in the plots) that coincides with the superconducting transition in tin.…”
Section: Resultsmentioning
confidence: 76%
“…The temperature dependence of the undoped and lightly doped crystals A and B agrees closely with data from earlier investigations on pure Mg 2 Sn single crystals, 8 the data from the heavily doped crystals are in broad agreement with data for Mg 2 Si and Mg 2 Ge crystals. [17][18][19] It is noted that the decrease in resistivity is consistent with the increase in carrier concentration, and any significant variations in the absolute resistivity values are likely due to uneven dopant distribution and the likely presence of microcracks. Samples with a small amount of free Sn show a transition to a lower residual resistivity at about 3.5 K (not shown in the plots) that coincides with the superconducting transition in tin.…”
Section: Resultsmentioning
confidence: 76%
“…Interestingly, Mg 2 Pb is a normal metal with a resistivity of about 200 lX cm at 300 K. These semiconducting compounds were first synthesized about 50 years ago and were shown to have excellent thermoelectric properties. [1][2][3][4] Intense interest during the last decade in thermoelectric materials, particularly the search for high figure of merit and environmentally friendly materials for medium-to high-temperature applications, has led to renewed interest in these compounds. Notably, the group 5,6 at Ioffe Physico-technical Institute has studied Mg 2 Si x Ge 1Àx solid solutions and showed that bulk polycrystalline samples possess a high dimensionless figure of merit ZT = (a 2 r/j)T % 1.1 at temperatures T = 600 K to 800 K, where a is the Seebeck coefficient, r is the electrical conductivity, j is the thermal conductivity of the material, and T is absolute temperature.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Recent work 7 has shown that ZT % 1.1 can be achieved in Mg 2 Si 1Àx Sn x solid solutions prepared by direct co-melting. Other preparation methods such as mechanical alloying, 8 solid-state reaction, 9 spark plasma sintering, 10 and hot pressing 11,12 have also been used.…”
Section: Introductionmentioning
confidence: 99%